The critical criminology companion - Anthony, Thalia; Cunneen, Chris, 1953- (Leichhardt, N.S.W. : Hawkins Press, 2008)
'This Companion presents the major debates and issues in Critical Criminology. It presents new research on crime, policy and the internationalisation of the criminal justice system. It sheds light on traditional debates in critical criminology through a confronting analysis of contemporary developments in criminal justice and criminology'--Publisher
Includes index and bibliographic references
Keywords: Criminology -- Australia; Criminology -- New Zealand; Crime -- Australia; Crime -- New Zealand; Crime analysis -- Australia; Crime analysis -- New Zealand